Microbially-accelerated consolidation of oil sands tailings. Pathway I: changes in porewater chemistry - Siddique, Tariq; Kuznetsov, Petr; Kuznetsova, Alsu; Arkell, Nicholas; Young, Rozlyn; Li, Carmen; Guigard, Selma E.; Underwood, Eleisha; Foght, Julia M. (Frontiers in Microbiology, 2014)
Dispersed clay particles in mine tailings and soft sediments remain suspended for decades, hindering consolidation and challenging effective management of these aqueous slurries. Current geotechnical engineering models of self-weight consolidation of tailings do not consider microbial contribution to sediment behavior, however, here we show that microorganisms indigenous to oil sands tailings change the porewater chemistry and accelerate consolidation of oil sands tailings. A companion paper describes the role of microbes in alteration of clay chemistry in tailings. Microbial metabolism in mature fine tailings (MFT) amended with an organic substrate (hydrolyzed canola meal) produced methane (CH4) and carbon dioxide (CO2). Dissolution of biogenic CO2 lowered the pH of amended MFT to pH 6.4 versus unamended MFT (pH 7.7). About 12% more porewater was recovered from amended than unamended MFT during 2 months of active microbial metabolism, concomitant with consolidation of tailings. The lower pH in amended MFT dissolved carbonate minerals, thereby releasing divalent cations including calcium (Ca2+) and magnesium (Mg2+) and increasing bicarbonate (HCO3-) in porewater. The higher concentrations increased the ionic strength of the porewater, in turn reducing the thickness of the diffuse double layer (DDL) of clay particles by reducing the surface charge potential (repulsive forces) of the clay particles. The combination of these processes accelerated consolidation of oil sands tailings. In addition, ebullition of biogenic gases created transient physical channels for release of porewater. In contrast, saturating the MFT with non-biogenic CO2 had little effect on consolidation. These results have significant implications for management and reclamation of oil sands tailings ponds and broad importance in anaerobic environments such as contaminated harbors and estuaries containing soft sediments rich in clays and organics.